A Meshfree Time-Splitting Approach for the Time-Fractional Burgers’ Equation - Erdal Korkmaz; Kenan Yildirim (Journal of Mathematics)
We consider to represent an algorithm for time-fractional Burgers’ equation utilizing the multiquadric-radial basis functions with the time-splitting technique. This algorithm is performed on the three examples. The numerical results indicated that the algorithm yields accurate approximate solutions of the time-fractional Burgers’ equation. The physical behavior of the obtained solutions is given with graphics, and the results showed that the obtained solutions are in good match with the solutions reported in the literature. The algorithm is accurate, flexible, and easy to implement.